Negotiating relationships and intimacy: Bangladeshi female migrant workers in Malaysia - Chakraborty, K. (2012)

(untitled)
This paper will review the context of female Bangladeshi migrant workers in Malaysia. The paper begins by reviewing position of women in Bangladeshi society. This exploration points to the possibilities of a negative reputation when women do venture overseas to work. Then the paper investigates the historical background of Bangladeshi migration to Malaysia. This investigation shows that migration is a highly gendered discourse in both countries. Moreover post-modern policies in Bangladesh and Malaysia have problematized ‘women workers’ in many ways. The paper will then detail the methods used in this research and how they are culturally and gender sensitive to the needs of women. Importantly the paper points to how different information and communication technologies (ICT) make it possible for women to develop various relationships. While the paper is based on early stage ethnographic research and preliminary finding it does point to gaps in our understanding of the lives of migrant women and concludes with a strong call for further research into their lives.